Annealing of radiation damage in zircons from Apollo 14 impact breccia 14311: Implications for the thermal history of the breccia - Pidgeon, R.; Merle, R.; Grange, M.; Nemchin, Alexander; Whitehouse, M. (WILEY-BLACKWELL, 2016)
Impact breccia 14311, was collected from the Apollo 14 landing site as a potential sample of the underlying Fra Mauro Formation. Published zircon U-Pb ages of >4000 Ma date the source material of the breccia and the apatite U-Pb age of ~3940 Ma is interpreted as dating thermal resetting of the apatite U-Pb systems. In this contribution we present new age information on the late stage thermal history of the breccia based on the annealing of radiation damage in the zircons. From Raman spectroscopic determination of the radiation damage within SIMS analytical spots on the zircons and the U and Th concentrations determined on these spots, we demonstrate that the radiation damage in the zircons has been annealed and we estimate the age of annealing at 3410 ± 80 Ma. This age is interpreted as a cooling age following heating of the breccia to above the annealing temperature of ~230 °C for stage 1 radiation damage in zircon, but below the temperature needed to reset the U-Pb system of apatite (~500 °C). It is proposed that this thermal event was associated with the prolonged period of Mare volcanism, from 3150 to 3750 Ma, that generated massive basalt flows in the vicinity of the sample location.